Bivariate and Multivariate Data Cloning through Non Linear Regression Models - Hussain, Sajid; Iqbal, Zafar; Muhammad Mansoor; Rashid Ahmed (Scientific Inquiry and Review, 2023)
Nonlinear regression analysis holds significant popularity in mathematical, engineering, and social science domains. Disciplines like financial matters, biology, and natural chemistry have broadly utilized nonlinear regression models (NLRMs). Cloned datasets have their own importance in such areas which provide the same fit of bivariate and multivariate nonlinear regression models for the actual datasets. This article presents a sequence of cloned datasets that give exactly the same fit of bivariate and multivariate nonlinear regression models.